Роль експресії Е-кадгерину в процесі інвазії папілярного раку щитоподібної залози - Хоперія, В. Г.; Ларін, О. С.; Васько, В. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
To determine whether the mesenchymal feature of invasive cancer cells is maintained in metastatic sites, we examined E-cadherin methylation and E-cadherin expression in 66 papillary thyroid cancer (PTC) samples and in 34 corresponding lymph node metastases (LNM). Hypermethylation of the E-cadherin gene promoter was detected in 39.3% of the PTCs, and loss of E-cadherin expression correlated with lymphocytic infiltration, extrathyroidal invasion and the presence of metastases. Comparing primary PTCs to the corresponding LNM, E-cadherin methylation status was identical in 60% of the cases. Loss of epigenetic silencing in LNMwas associated with a gain of E-cadherin expression. Hypermethylation of the E-cadherin gene promoter was detected in thyroid cancer cell lines with mesenchymal-like morphology. Loss of E-cadherin expression in these cells correlated with high migratory ability. Inhibition of RAS/ERK or PI3K/AKTsignaling decreased the migratory ability of these cells but did not induce E-cadherin expression. In the cells with epithelial-like morphology, treatments with phorbolester or tumor necrosis factor (TNF)-α resulted in translocation of membranous E-cadherin to the cytoplasm and induction of migration. E-cadherin promoter methylation status and E-cadherin expression were not affected by TNF. Together, dynamic changes in E-cadherin methylation occur during metastatic progression in thyroid cancer. Epigenetic mechanisms and TNF-inducible signaling independently contribute to the regulation of E-cadherin expression and localization. These mechanisms may play a role in the induction of EMTin primary tumors and in the conversion from the mesenchymal to the epithelial phenotype in metastases.